2008
DOI: 10.1038/onc.2008.438
|View full text |Cite|
|
Sign up to set email alerts
|

HAND1 gene expression is negatively regulated by the High Mobility Group A1 proteins and is drastically reduced in human thyroid carcinomas

Abstract: HMGA1 proteins exert their major physiological function during embryonic development and play a critical role in neoplastic transformation. Here, we show that Hand1 gene, which codes for a transcription factor crucial for differentiation of trophoblast giant cells and heart development, is upregulated in hmga1 minus embryonic stem cells. We demonstrate that HMGA1 proteins bind directly to Hand1 promoter both in vitro and in vivo and inhibit Hand1 promoter activity. We have also investigated HAND1 expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…HMGA1 downregulation by siRNA enhanced transcriptional activity of p53, and increased thyroid cancer apoptosis (37). It was also reported that HMGA1 proteins can inhibit Hand1 promoter activity, and HMGA1 overexpression exerts an important role on HAND1 silencing in differentiated thyroid carcinomas (38). In addition, HMGA1 silencing decreased the expression of vimentin and Snail, increased the expression of E-cadherin in triple-negative breast cancer MDA-MB-231 cells (4).…”
Section: Discussionmentioning
confidence: 99%
“…HMGA1 downregulation by siRNA enhanced transcriptional activity of p53, and increased thyroid cancer apoptosis (37). It was also reported that HMGA1 proteins can inhibit Hand1 promoter activity, and HMGA1 overexpression exerts an important role on HAND1 silencing in differentiated thyroid carcinomas (38). In addition, HMGA1 silencing decreased the expression of vimentin and Snail, increased the expression of E-cadherin in triple-negative breast cancer MDA-MB-231 cells (4).…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate, HMGA1 was reported to repress HAND1 (Heart and Neural Crest Derivatives expressed 1) , a member of the Twist subfamily of basic helix-loop-helix (bHLH) transcription factors [215]. Studies in Hand1 null mice indicate that it plays a critical role in placenta formation and cardiac morphogenesis in the ventricular chambers [215] Hand1 expression was reported to be enhanced in Hmga1 null mice and HMGA1 binds to the Hand1 promoter, both in vitro and in vivo , as demonstrated by in gel shift analysis and chromatin immunoprecipitation. Transfection experiments showed that HMGA1 represses HAND1 promoter expression.…”
Section: Hmga1 Transcriptional Targetsmentioning
confidence: 99%
“…Moreover , HMGA1 overexpression was reported to be associated with DNA methylation of the HAND1 promoter in anaplastic thyroid carcinomas in advanced tumors. HAND1 is also silenced in gastric, colorectal, and pancreatic cancers [215218]. …”
Section: Hmga1 Transcriptional Targetsmentioning
confidence: 99%
“…Multiple molecular mechanisms contribute to the oncogenic activities of HMGAs. These mechanisms include uncontrolled cell cycling (Tessari et al, 2003), enhancement of transcription factor DNA-binding activity (Vallone et al, 1997), inhibition of apoptosis activity (Esposito et al, 2012), impairment of the DNA damage response (Pentimalli et al, 2008), promotion of inflammatory mediator production (Hillion et al, 2008; Perrella et al, 1999), regulation of cancer stem cells (Yanagisawa and Resar, 2013), downregulation of potential tumor-suppressor genes (Martinez Hoyos et al, 2009), upregulation of epithelial-mesenchymal transition (Morishita et al, 2013; Thuault et al, 2006), functioning as a competing endogenous RNA for microRNA (e.g., let-7 and MicroRNA-137) (Kumar et al, 2014; Liang et al, 2013a), and enhancement of autophagy-mediated aerobic glycolysis (Ha et al, 2012a). However, HMGAs also exerts anti-proliferative properties in some cells (Fedele et al, 2006), calling for further study of HMGA1 as potential therapeutic agent in cancer treatment.…”
Section: Introduction and Historical Backgroundmentioning
confidence: 99%